1999
DOI: 10.1002/pc.10343
|View full text |Cite
|
Sign up to set email alerts
|

Processing of highly elastomeric toughened cyanate esters through a modified resin transfer molding technique

Abstract: Model cyanate ester resins containing different quantities of epoxy functional butadiene‐acrylonitrile rubber (ETBN) to improve the fracture performance were developed as matrices for composites. With the elastomeric modification, the resin systems exhibited rheological characteristics inappropriate for laminate fabrication by conventional resin transfer molding (RTM). To fabricate the carbon fiber based laminates in one liquid molding operation successfully, a process named bleed resin transfer molding (BRTM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…As has been reported previously, highly crosslinked matrices with a tough second phase rarely lead to sufficient increases in mode I fracture toughness. [27][28][29] Optical microscopy of polished crosssections revealed that all four materials were well impregnated and essentially void free. It was found that a second phase (dark areas) was formed in the PS-modified cyanate ester (Fig.…”
Section: Properties Of Unconditioned Materialsmentioning
confidence: 98%
“…As has been reported previously, highly crosslinked matrices with a tough second phase rarely lead to sufficient increases in mode I fracture toughness. [27][28][29] Optical microscopy of polished crosssections revealed that all four materials were well impregnated and essentially void free. It was found that a second phase (dark areas) was formed in the PS-modified cyanate ester (Fig.…”
Section: Properties Of Unconditioned Materialsmentioning
confidence: 98%
“…So, appreciative modification is required to improve its toughness. Various methods such as copolymerization with flexible monocyanates monomer [6] , maleimide monomer [7] , utilization of reactive liquid rubber [8][9][10] , oligodimethylsiloxane [11] , thermoplastics [12] , and preparation of semi-interpenetration networks (S-IPNs) [13] have been proven useful for the toughness of CE resins. Besides, the incorporation of inorganic nanostructures with high strength, stiffness and enormous aspect ratio, such as carbon nanotubes [14] , clay [15] , rectorite [16] and montmorillonite [17,18] , also possess potential application for the toughness of the CE resins.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, several attempts have been made to improve the toughness of cyanate ester by adding elastomers or thermoplastics [5][6][7][8][9][10][11][12]. Traditionally, the most successful method has been the addition of a suitable elastomer to the uncured resin [2,[5][6][7][8]. However, in the last years, the modification with high-performance thermoplastics has been more investigated because of the advantage, as compared to rubber modification, that there is no reduction in thermal and mechanical properties of the cyanate matrix [5][6][7][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…High performance polymer matrix composites based on carbon fiber and cyanate ester resins have gained a great deal of attention in the aerospace industry because of their excellent thermal and dielectric properties also having similar processability to conventional epoxy based composites [1][2][3]. Nevertheless, although cyanate ester resins are known to be relatively tough compared with other thermosetting matrices, some applications require improved fracture resistance [4].…”
Section: Introductionmentioning
confidence: 99%